The changing demographics of the orthotist/prosthetist workforce in Australia: 2007, 2012 and 2019 - Emily Ridgewell; Leigh Clarke; Sarah Anderson; Michael P. Dillon (BMC, 2021)
Abstract Background Previous Australian workforce analyses revealed a small orthotist/prosthetist workforce with a low number of practitioners per 100,000 Australians. In recent years, initiatives were implemented to increase relative workforce size, including a government-led change in immigration policy to facilitate entry of experienced internationally trained orthotist/prosthetists into the Australian workforce. Given these changes, this project aimed to compare demographics of the orthotist/prosthetist workforce in Australia and each state/territory between 2007, 2012 and 2019. Methods This quasi-experiment analysed data from the Australian Orthotic Prosthetic Association (AOPA) database of certified orthotist/prosthetists, to compare changes in the absolute number of practitioners and the number of practitioners per 100,000 population, as well as practitioner age, gender and service location (i.e., metropolitan, regional/remote) across three time points, with a breakdown by each Australian state and territory. Results Between 2007 and 2019, the number of orthotist/prosthetists per 100,000 population increased 90%. Average age reduced significantly between 2007 (41.5 years) and 2019 (35 years) (p = 0.001). While the proportion of female practitioners increased significantly between 2007 (30%) and 2019 (49%), and between 2012 (38%) and 2019 (49%) (p < 0.05); only 22% of the female workforce is over 40 years of age. The proportion of practitioners servicing a regional/remote location did not change over time (range 13-14%). Conclusions Between 2007 and 2019, the national orthotist/prosthetist workforce increased at a rate that exceeded Australia's population growth, became younger, and more female. However, the number of practitioners per 100,000 population remains below international recommendations; particularly in states outside of Victoria and Tasmania, and in regional/remote areas. In addition, low numbers of mid-late career female practitioners suggest challenges to retention of this particular cohort. These data can help inform workforce initiatives to retain a younger and more female workforce, and improve access to orthotic/prosthetic services.